FACTORS THAT CONTRIBUTE TOWARDS POOR PERFORMANCE OF STUDENTS IN SCIENCE IN RURAL SCHOOLS IN TSHOLOTSHO DISTRICT IN MATABELELAND PROVINCE IN ZIMBABWE - NDLOVU, FRANCIS (IJRDO- Journal of Educational Research, 2017)
This study sort to investigate learners’ attributions on high failure in science examinations inrural secondary schools in Tsholotsho district in Matabeleland North Province of Zimbabwewhich has a student population of 2300 at Ordinary Level. A total of 400 respondents were usedof which 240 were girls and 160 were boys. The research instrument used was the questionnairewhich had both close ended and open ended questions. Descriptive statistical analysis was usedto interpret data. The study revealed that pupils attributed their failure mainly to lack of materialresources, poor teaching methods, bad teacher behaviour, and poor grounding in the subject atlower levels as well as their fear of the subject. The study recommends that the Ministry ofEducation should embark on serious in service training science teachers. Teachers should alsoembark on team teaching to assist each other on the subject. Finally, pupils should be motivatedto view science like the rest of the subjects in the school curriculum.